RESPON NETIZEN TERHADAP NOVEL CYBERSASTRA “MAJDULIN“ DALAM APLIKASI E-READER ABJAD (Pendekatan Reader Response) - Silmi Ibnit; Siti Muslikah (Bahasa dan Sastra Arab, Fakultas Adab dan Humaniora, UIN Sunan Gunung Djati, 2023)
This research aims to determine the response of netizens as readers, who provide clauses, sentences, and discourse in the form of comments in one of the cyber literary novels